The effect of ozone exposure on the release of eicosanoids in guinea-pig BAL fluid in relation to cellular damage and inflammation - H. J. M. Van Hoof; F. J. Zijlstra; H-P. Voss; I. M. Garrelds; J. A. M. A. Dormans; L. Van Bree; A. Bast (Mediators of Inflammation)
The observed effects after ozone exposure strongly depend on ozone concentration and exposure time. We hypothesized that depending on the O3 exposure protocol, mainly either an oxidant damage or an inflammation will determine the O3 toxicity. We compared two different ozone exposure protocols: an acute exposure (3 ppm 2 h) for studying the oxidant damage and an exposure (1 ppm 12 h) where an inflammatory component is also probably involved. We measured LDH activity and protein and albumin exudation as markers for cellular damage. After the acute exposure an increase in LDH activity was measured and after exposure to 1 ppm ozone for 12 h the exudation of protein and albumin was also enhanced. The histological examinations showed a neutrophilic inflammatory response only after exposure to 1 ppm ozone for 12 h. The acute exposure protocol resulted in an increased release of PGE2, PGD2, PGF2α and 6-ketoPGF1α whereas exposure to 1 ppm ozone for 12 h led to an additional release of LTB4. No effects were measured on the release of TxB2 and LTC4/D4/E4. These changed amounts of eicosanoids will probably contribute to the ozone-induced lung function changes.